2021
DOI: 10.1111/tbed.14032
|View full text |Cite
|
Sign up to set email alerts
|

Feline chaphamaparvovirus in cats with enteritis and upper respiratory tract disease

Abstract: Feline chaphamaparvovirus (FeChPV) is a novel parvovirus, first discovered in a multi‐facility feline shelter in Canada in 2019, during an outbreak of acute gastro‐enteritis (AGE) in cats, and detected at high prevalence (47.0%) in faecal samples. Whether this finding was anecdotal or similar viruses are common components of feline virome is still unclear. Also, the potential impact of this virus on feline health is uncertain. Herewith, a case–control study was performed to investigate whether this novel parvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
49
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(56 citation statements)
references
References 38 publications
5
49
2
Order By: Relevance
“…Our findings of the prevalence of FeChPV in the oropharyngeal swabs of healthy cats supported theirs, which was 1.42% (2/70) and 4.28% (6/140), respectively. The NP nt and aa sequence of the FechaV/Tur-2020/2 and FechaV/Tur-2020/68 isolates obtained from this study shared 92.38–97.14% and 98.08–99.03% identity, respectively, with FeChPVs (313R/2019/ITA, 49E/2019/ITA, and 284R/2019/ITA) identified in Italy by Di Profio et al ( 2021 ). The results were also similar for the VP gene sequence of the FechaV/Tur-2020/68 strain (> 98% nt and > 96% aa identities).…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Our findings of the prevalence of FeChPV in the oropharyngeal swabs of healthy cats supported theirs, which was 1.42% (2/70) and 4.28% (6/140), respectively. The NP nt and aa sequence of the FechaV/Tur-2020/2 and FechaV/Tur-2020/68 isolates obtained from this study shared 92.38–97.14% and 98.08–99.03% identity, respectively, with FeChPVs (313R/2019/ITA, 49E/2019/ITA, and 284R/2019/ITA) identified in Italy by Di Profio et al ( 2021 ). The results were also similar for the VP gene sequence of the FechaV/Tur-2020/68 strain (> 98% nt and > 96% aa identities).…”
Section: Discussionsupporting
confidence: 61%
“…In the same study, FeChPV was investigated by PCR in oropharyngeal clinical samples of 183 cats with URTD (57%) and 140 healthy cats (43.3%) in 2014–2017, and FeChPV DNA was detected in 12 clinical samples, six of which belonged to healthy animals. It was reported that there was no statistically significant relationship between FeChPV and URTD (Di Profio et al 2021 ). Our findings of the prevalence of FeChPV in the oropharyngeal swabs of healthy cats supported theirs, which was 1.42% (2/70) and 4.28% (6/140), respectively.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In a recent case-control study carried out in Italy, FeChPV has been identified from fecal and respiratory samples of cats, displaying a correlation with acute gastroenteritis [110]. Since the Italian strains shared more than 97.7% aa identity in the NS1 protein with Canadian prototype viruses, they have been clustered into a monophyletic, welldistinguished species (Fechavirus) with respect to the FeChPV strains found in China and currently classified as the species Carnivore chaphamaparvovirus 1 [2,18,19,110].…”
Section: Chaphamaparvovirusesmentioning
confidence: 99%